Chiggers (Acariformes: Trombiculoidea) do not increase rates of infection by Batrachochytrium dendrobatidis fungus in the endemic Dwarf Mexican Treefrog Tlalocohyla smithii (Anura: Hylidae). (April 2020) - Jacinto-Maldonado, M.; García-Peña, G.E.; Paredes-León, R.; Saucedo, B.; Sarmiento-Silva, R.E.; García, A.; Martínez-Gómez, D.; Ojeda, M.; Del Callejo, E.; Suzán, G.
Abstract: Amphibian populations are globally declining at an alarming rate, and infectious diseases are among the main causes of their decline. Two micro-parasites, the fungus Batrachochytrium dendrobatidis (Bd) and the virus Ranavirus (RV) have caused mass mortality of amphibians and population declines. Other, less understood epizootics are caused by macro-parasites, such as Trombiculoidea chiggers. Infection with chiggers can affect frog behavior and survival. Furthermore, synergistic effects of co-infection with both macro and micro-parasites may lead to higher morbidity. To better understand these potential synergies, we investigated the presence and co-infection by chiggers, Bd and RV in the endemic frog Tlalocohyla smithii ( T. smithii ). Co-infection of Bd, RV, and/or chiggers is expected in habitats that are suitable for their co-occurrence; and if infection with one parasite facilitates infection with the others. On the other hand, co-infection could decrease if these parasites were to differ in their micro-environmental requirements (i.e. niche apportionment). A total of 116 frogs of T. smithii were studied during 2014 and 2016 in three streams within the Chamela-Cuixmala Biosphere Reserve in Jalisco, Mexico. Our results show that 31% of the frogs were infected with Trombiculoidea chiggers ( Hannemania sp. and Eutrombicula alfreddugesi ); Hannemania prevalence increased with air temperature and decreased in sites with high canopies and with water pH values above 8.5 and below 6.7. Bd prevalence was 2.6%, RV prevalence was 0%, and none of the frogs infected with chiggers were co-infected with Bd. Together, this study suggests that chiggers do not facilitate infection with Bd, as these are apportioned in different micro-habitats. Nevertheless, the statistical power to assure this is low. We recommend further epidemiological monitoring of multiple parasites in different geographical locations in order to provide insight on the true hazards, risks and conservation options for amphibian populations. Graphical abstract: Image 1 Highlights: This is the first report of Hannemania sp. and Eutrombicula alfreddugesi chiggers in Tlalocohyla smithii . 31% of the frogs ( Tlalocohyla smithii ) were infected with Hannemania sp. and Eutrombicula alfreddugesi . Hannemania prevalence rose with air temperature and fell at sites with high canopies and water pH over 8.5 and below 6.7. Batrachochytrium dendrobatidis prevalence was 2.6% and Ranavirus prevalence was 0%. None of the frogs infected with chiggers were coinfected with Bd.